IMPLEMENTATION OF DRUG SUPPLY CHAIN MANAGEMENT IN THE PRACTICE OF THT-KL SPECIALISTS - Ragil Andika Putra; Havid Syafwan; Akmal Nasution (STMIK Royal, 2023)
Abstract: THT-KL Specialist Practice Dr. Julius Dariar is a practice that provides medical services and sells medicines for ear, nose, throat and head and neck surgery. The problem experienced is that drug preparation is still done manually, so it requires time, effort and a high level of accuracy and precision. This study aims to design an information system that can process incoming and outgoing drug supply data at the THT Specialist Practice-KL Dr. Julius Dariar by implementing Supply Chain Management. The result of his research is the design of a website-based Supply Chain Management application that can be used by users in managing drug stocks in the practice of THT-KL specialist Dr. Julius Dariar. Keywords: Practice; SCM; Specialist; THT-KL Abstrak: Praktek Spesialis THT-KL Dr. Julius Dariar merupakan salah satu praktek yang melayani jasa pengobatan dan penjualan obat mengenai telinga, hidung, tenggorokan, dan bedah kepala leher. Adapun masalah yang dialami ialah penyiapan obat masih dilakukan dengan manual, sehingga memerlukan waktu, tenaga serta tingkat ketelitian dan kecermatan yang tinggi. Penelitian ini bertujuan untuk merancang sistem informasi yang dapat mengolah data persediaan obat masuk dan keluar di Praktek Spesialis THT-KL Dr. Julius Dariar dengan menerapkan Supply Chain Management. Hasil penelitiannya adalah rancangan aplikasi Supply Chain Management berbasis website yang dapat digunakan oleh user dalam pengelolaan stok obat-obatan pada praktik spesialis THT-KL dr.Julius Dariar. Kata kunci: Praktik; SCM; Spesialis; THT-KL